(untitled) (Revista de História da UEG (REVHIST), 2025)
This article aims to discuss the search for land ownership by Brazilians in Paraguay and its consequences until the return migration of small farmers. This is an oral history study, based on interviews carried out from July 2018 to January 2019, in districts of the Department of Alto Paraná in the case of Santa Rita, Naranjal and San Alberto, and border municipalities in Paraná, in the case of Foz do Iguaçu, Santa Terezinha de Itaipu and Missal. In this sense, we divided our work into three sections. Firstly, we deal with the search for land ownership among southern immigrants. Next, we cover some of the work on these properties in the early days in Paraguay. Finally, in the third section, we reflect on the factors that influenced return migration. It is concluded that there was, among these immigrants, a generational and cultural element that made them seek to obtain ownership of land for cultivation. Furthermore, if when emigrating to Paraguay, the Brazilian context made it difficult to acquire land due to the high costs, due to modernization in the countryside and the attractive investment in agricultural areas in the Eastern region of Paraguay; In a few decades, the process of modernization and subsequent agribusiness, due to high investment costs, will make it difficult for small farmers to remain in the field. Keywords: Paraguay; Land ownership; Immigrants.